Extinction and nebular line properties of a Herschel-selected lensed dusty starburst at z = 1.027 - Timmons, Nicholas; Cooray, Asantha; Nayyeri, Hooshang; Casey, Caitlin; Calanog, Jae; Ma, Brian; Messias, Hugo; Baes, Maarten; Bussmann, R. Shane; Dunne, Loretta; Dye, S.; Eales, Steve; et al. (American Astronomical Society, 2015)
We present Hubble Space Telescope Wide Field Camera 3 (WFC3) imaging and grism spectroscopy observations of the Herschel-selected gravitationally lensed starburst galaxy HATLASJ1429-0028. The lensing system consists of an edge-on foreground disk galaxy at z = 0.218 with a nearly complete Einstein ring of the infrared luminous galaxy at z = 1.027. The WFC3 spectroscopy with G102 and G141 grisms, covering the wavelength range of 0.8–1.7 μm, resulted in detections of Hα + [Nii], Hβ, [Sii], and [Oiii] for the background galaxy from which we measure line fluxes and ratios. The Balmer line ratio Hα/Hβ of 7.5 ± 4.4, when corrected for [Nii], results in an extinction for the starburst galaxy of . The Hα-based star formation rate (SFR), when corrected for extinction, is 60 ± 50 yr−1, lower than the instantaneous SFR of 390 ± 90 yr−1 from the total IR luminosity. We also compare the nebular line ratios of HATLASJ1429-0028 with other star-forming and sub-millimeter bright galaxies. The nebular line ratios are consistent with an intrinsic ultra-luminous infrared galaxy with no evidence for excitation by an active galactic nucleus (AGN). We estimate the metallicity, 12 + log(O/H), of HATLASJ1429-0028 to be 8.49 ± 0.16. Such a low value is below the average relation for stellar mass versus metallicity of galaxies at for a galaxy with a stellar mass of . The combination of high stellar mass, the lack of AGN indicators, low metallicity, and the high SFR of HATLASJ1429-0028 suggest that this galaxy is currently undergoing a rapid formation.